Antitumoral potential, antioxidant activity and carotenoid content of two Southern Italy tomato cultivars extracts: San Marzano and Corbarino. Issue 2 (12th June 2017) - Barone, Daniela; Cito, Letizia; Tommonaro, Giuseppina; Abate, Agnese A.; Penon, Danila; De Prisco, Rocco; Penon, Antonella; Forte, Iris M.; Benedetti, Elisabetta; Cimini, Annamaria; Indovina, Paola; Nicolaus, Barbara; et al.
Abstract : Gastric cancer represents a diffuse and aggressive neoplasm, whose mortality index is among the highest in the world. Predisposing factors are E‐cadherin mutations, Helicobacter pylori infection, and a diet rich in salted and smoked food, with a low intake of fresh fruits and vegetables. Here, we analyzed the effect of total lipophilic extracts of two Southern Italy tomato varieties, San Marzano and Corbarino, on an in vitro model of gastric cancer, YCC‐1, YCC‐2 and YCC‐3 cell lines, characterized by different aggressiveness. Our results showed a possible role of these two varieties of tomatoes against typical neoplastic features. The treatment with tomato extracts affected cancer cell ability to grow both in adherence and in semisolid medium, reducing also cell migration ability. No toxic effects were observed on non‐tumoral cells. We found, on gastric cancer cell lines, effects on both cell cycle progression and apoptosis modulation. The extent of antineoplastic effects, however, did not seem to correlate with the carotenoid content and antioxidant activity of the two tomato varieties. Our data indicate that San Marzano and Corbarino intake might be further considered as nutritional support not only in cancer prevention, but also for cancer patient diet. Abstract : We analyzed the effect of total lipophilic extracts of two Southern Italy tomato varieties, San Marzano and Corbarino, on an in vitro model of gastric cancer. The treatment with tomato extracts affected cancer cell ability to grow both in adherence and in semisolid medium, reducing also cell migration ability; these effects were caused by both cell cycle progression and apoptosis modulation. Data showed a possible role of these two varieties of tomatoes against typical neoplastic features.